ANALISIS MISKONSEPSI SISWA DALAM MENJAWAB SOAL-SOAL PADA MATERI FLUIDA STATIS - Yohanis Taruly; Haratua Tiur Maria; Syaiful B Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the factors of students' conceptualerrors in answering questions on static fluid material. The researchmethod used is to collect as much as possible regarding theconceptual errors made by students in answering questions onstatic fluid material and its factors, so the method used isdescriptive. The simple research was the students of class IX MIA1 SMA Negeri 2 Sintang, totaling 15 students who worked on thequestions as representatives. The ability to solve students'conceptual errors was measured using 10 multiple-choice testinstruments. The data obtained on the ability to solve conceptualerrors of students on average 22% guessed, 45.33% experiencedmisconceptions and 32.67% students understood the concept. Theresults of statistical tests show that students who experiencemisconceptions are greater than those who understand conceptsand guess, this shows that there are still many students who do notunderstand the concept of static fluid, so that it will be a futurelearning guide to improve students' understanding of concepts.